2012
DOI: 10.1007/s00586-012-2578-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of hangman’s fracture with percutaneous transpedicular screw fixation

Abstract: The fluoroscopically assisted percutaneous C2 transpedicular screw fixation method is a technically feasible and minimally invasive technique for hangman's fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The percutaneous technique presented here seems to be equally safe and effective as the open procedures previously reported, without the pedicle wall perforation rate of 15% associated with the percutaneous approach reported by Wu et al 32 We again highlight the value of intraoperative CT imaging and neuronavigation in this procedure. As mentioned, fracture alignment as seen on CT images may change due to differences in preoperative to intraoperative patient position.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The percutaneous technique presented here seems to be equally safe and effective as the open procedures previously reported, without the pedicle wall perforation rate of 15% associated with the percutaneous approach reported by Wu et al 32 We again highlight the value of intraoperative CT imaging and neuronavigation in this procedure. As mentioned, fracture alignment as seen on CT images may change due to differences in preoperative to intraoperative patient position.…”
Section: Discussionsupporting
confidence: 68%
“…Wu et al 32 reported the use of percutaneous transpedicular screw fixation for hangman's fractures; they performed preoperative imaging to ascertain entry points, angles, and distances for screw fixation without the use of neuronavigation. In place of intraoperative neuronavigation, they used measurements, angles, and trajectories established from the preoperative CT scans to plot their percutaneous screw course.…”
Section: Discussionmentioning
confidence: 99%
“…The use of percutaneous transpedicular screw fixation in the treatment of Hangman's fracture (traumatic spondylolisthesis of the axis) described by Wu et al [31] describes a useful technique. Although only ten patients are reported, and it is clear that all such fractures are suitable, modern imaging can allow this technique, and clearly there is much less morbidity.…”
Section: Fracturesmentioning
confidence: 99%
“…Hangman's fractures account for 15% to 20% of cervical spine injuries. This fracture type was first described in individuals sentenced to death by hanging but is now more often due to seatbelt loading during traffic accidents [7,9]. The mortality rate in patients with hangman's fracture due to any cause is 7% at the most [5].…”
Section: Discussionmentioning
confidence: 99%